ANALYSIS OF HIGH RISK FACTORS FOR NON-COMMUNICABLE DISEASE, STROKE IN THE SIDOARJO DISTRICT HEALTH SERVICE - Widarti, Luluk; Afif Hilmi Masyfahani, Muhammad; Sulystiono, Dony; Suprihatin, Kusmini; Siagian, Hotmaida; Maemonah, Siti (Universitas Airlangga, 2024)
Introduction: Stroke is the number one cause of disability and the number three cause of death in the world. The burden caused by stroke is mainly caused by disability (a public health problem) which also creates a high cost burden for the sufferer, their family, society, and the government. Methods: The type of research in this research is a case study using quantitative descriptive design methods. This research was conducted in the working area of